The Modernist Impulse in American Protestantism - Hutchison, William R. (Book collections on Project MUSE., 1992)
This landmark study of American religion, recipient of the National Religious Book Award in 1976, is being brought back into print with an updated bibliography. The Modernist Impulse in American Protestantism traces the history of American Protestant thought from the early part of the nineteenth century to the present. William R. Hutchison deals especially with the ""modernist"" movement that flourished in the years around 1900, and with the colorful personalities and disputes associated with that movement.